Effect of adjuvants and nitrogen sources on in vitro shoot regeneration and clonal propagation of medicinally important plant Eryngium foetidum L - G.S, Nagananda; S, Rajath; Mathew, Ruby. K.; Rajan, S. Sundara (Research in Biotechnology, 2012)
In vitro regeneration of medicinally important plant Eryngium foetidum L. was established by developing a protocol for successful faster clonal propogation. Young leaves of the plant were taken and cultured on 1x MS medium supplemented with different concentrations and combinations of 6- Benzyl amino purine (BAP), 1-Napthylacetic acid (NAA) and Kinetin (Kin). Leaves cultured on 2mg/L BAP and 1mg/L NAA showed better response in short duration of time when compared to other concentrations and combinations. Induced shoots obtained from standardized media were used as explant and cultured on 1x MS medium containing 2mg/L BAP and 1mg/L NAA fortified with 10% of different nitrogen sources likeÃ‚Â tryptone, peptone, beef extract, yeast extract and adjuvants like coconut milk, tomato juice and banana pulp to observe the growth response. It was observed that media containing 10% coconut milk and 10% peptone showed better result when compared to other adjuvants and nitrogen sources. The well developed plantlets were hardened and successfully transferred to the field with 85% survival rate.